Gastric TFF1 Expression from Acute to Chronic Helicobacter Infection - Esposito, Roberta; Morello, Silvana; Vllahu, Megi; Eletto, Daniela; Porta, Amalia; Tosco, Alessandra (Frontiers in Cellular and Infection Microbiology, 2017)
TFF1, a mucin-associated secreted peptide of gastric mucous cells, is known as a protective agent for stomach epithelium under different stimuli, but its role upon Helicobacter infection is still not clear. In this paper we characterized TFFs expression, with particular attention to TFF1, under Helicobacter infection in gastric cell lines. A mouse model was used to distinguish TFF1 mRNA expression between acute and chronic stages of Helicobacter infection. Our results show that TFF1 expression is induced in infected cells; in addition, the inflammatory response upon Helicobacter infection is inversely associated to pre-existing TFF1 protein levels. In infected mice, TFF1 is initially upregulated in gastric antrum in the acute phase of infection, along with IL-1β and IL-6. Then, expression of TFF1 is gradually silenced when the infection becomes chronic and IFN-γ, CXCL5 and CXCL15 reach higher levels. Our data suggest that TFF1 might help cells to counteract bacteria colonization and the development of a chronic inflammation.